2008
DOI: 10.1002/mar.20230
|View full text |Cite
|
Sign up to set email alerts
|

Can consumers recognize misleading advertising content in a media rich online environment?

Abstract: The worldwide growth and acceptance of e-commerce provides consumers with the opportunity to shop in computer-mediated interactive environments that simulate direct product experience. However, the phenomenal growth in advertising on the Internet and marketers' ability to rapidly change the content of online ads also create concerns about consumers being exposed to a plethora of potentially misleading advertisements on the Internet. Relatively little research to date has focused on how consumer beliefs are sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Regarding the use of VR in advertising, studies focus on comparing the effects of traditional brand communications with VR brand communications. The findings support the positive effects of VR-enhanced approaches on purchase intentions (Verhagen et al, 2014;Li, Daugherty & Biocca, 2002;Suh & Lee, 2005), with the mediating effects associated with brand knowledge (Suh & Lee, 2005;Mitra, Raymond & Hopkins, 2008) and brand attitude (Li, Daugherty & Biocca, 2002;Suh & Lee, 2005;Dobrowolski et al, 2014) resulting from the increased affective dimension of the VR brand experience.…”
Section: T7 Communication and Social Media Studies On This Topic Are supporting
confidence: 61%
See 1 more Smart Citation
“…Regarding the use of VR in advertising, studies focus on comparing the effects of traditional brand communications with VR brand communications. The findings support the positive effects of VR-enhanced approaches on purchase intentions (Verhagen et al, 2014;Li, Daugherty & Biocca, 2002;Suh & Lee, 2005), with the mediating effects associated with brand knowledge (Suh & Lee, 2005;Mitra, Raymond & Hopkins, 2008) and brand attitude (Li, Daugherty & Biocca, 2002;Suh & Lee, 2005;Dobrowolski et al, 2014) resulting from the increased affective dimension of the VR brand experience.…”
Section: T7 Communication and Social Media Studies On This Topic Are supporting
confidence: 61%
“…In sum, the articles included in this topic highlight conceptual contributions and experimental designs, with the VR technologies tested being limited to 3D image rotation (Li, Daugherty & Biocca, 2002;Suh & Lee, 2005;Verhagen et al, 2014) and sound animation (Mitra, Raymond & Hopkins, 2008;Dobrowolski et al, 2014). Few studies (about 10%) use VR plug-ins (Suh & Lee, 2005;Dobrowolski et al, 2014).…”
Section: T7 Communication and Social Media Studies On This Topic Are mentioning
confidence: 99%
“…The scale demonstrated good psychometric properties based on findings from a variety of reliability and validity tests. Recently, Mitra et al (2008) analyzed how consumer's beliefs are shaped by online advertising (truthful versus misleading) claims and affected by media richness. Their lab study, conducted with students, showed that the deception potential is greater when consumer's involvement is low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing body of literature has emphasized the importance of specific aspects of online shopping environments on consumer responses. In particular, the implications of information abundance (Ariely, 2000; Jepsen, 2007; Lee & Lee, 2004), the impact of features afforded by the interactivity of the medium (e.g., Fiore, Jin, & Kim, 2005; Li, Daugherty, & Biocca, 2001; Mitra, Raymond, & Hopkins, 2008), the importance of navigation cues (Dailey, 2004), and the differential impact of verbal or visual content (Kim & Lennon, 2008) have been considered. These studies provide valuable insights into the potential effects of these features.…”
Section: Introductionmentioning
confidence: 99%